The factor that affecting the ability of middle income household to have affordable home ownership in urban area, Kuala Lumpur / Syahidah Sehat - Sehat, Syahidah (2013)
The main purpose of this study is to examine the factor that affecting the ability of middle income household to have affordable home ownership in urban area. The factor such as macro factor (location, loan interest rates charged effect and financing facilities) and micro factor (demographic behaviour) are been used as the independent variables for this study. The distribution of questionnaire has been used to collect the information needed from the respondent which is specifically to the middle income group. From 100 questionnaires that have been distributed, only 87 questionnaires can be used. Then, the questionnaires were analyzed using SPSS version 17 and 19 program. Those variables were testing by Pearson Correlation to find the significant relationship between the dependent and independent variables. The result from the findings represents that all independent variables is significant towards dependent variables and can be used in making prediction on this study. This topic was chosen by researcher is because the researcher wants to know the reasons on why most of the middle income earners cannot afford to have affordable home ownership in urban areas, Kuala Lumpur.